The Impact of Compressor Wash Maintenance on the Rolls Royce M250-B17F Engine Performance of Grob G 120TP-A Aircraft - Prakoso, Agung; Lukito, Indro; Junaidin, Buyung; Wibowo, Teguh; Budiono, Cyrilus Sukaca (Vortex, 2026)
The Grob G 120TP-A is a training aircraft powered by the Rolls Royce M250-B17F engine with limited aerobatic capabilities. To optimize its flight performance, maintenance procedures such as compressor wash are essential. Compressor washing is conducted periodically every 100 flight hours to clean the compressor blades from contaminants caused by humidity and salt particles. This study used thermodynamic analysis to evaluate the increase in thrust power and effective power after compressor washing at different Outside Air Temperatures (OAT). The results indicate that after compressor washing, the thrust power increased by 4.3% and the effective power increased by 0.3%, demonstrating the importance of routine maintenance in sustaining optimal engine and aircraft performance.